Canais de distribuição para produtos da agricultura familiar: um estudo em hortaliças. - Machado, Melise Dantas (Universidade Federal de São Carlos, 2004)
The intention of this work is to study marketing channel for products proceeding from small holders agriculture. Considering that small holders agriculture,in São Paulo State, represents 95% of the production of fresh vegetables, the focus this research falls again on the marketing channel of the related production. Initially a background revision was become about some topics to the subject, in special: marketing channels and small holders agriculture. In the empirical research, a multi-case study was made with small holders agriculture and involved companies in the distribution of fresh vegetables, in two subsequent phases. In the first, searched to understand the particularitities of small holders agriculture. Then, twenty-four small holders agriculture and five specialists of the area had been interviewed. In the second phase, twenty-four members of the retail market, wholesale market and food service companies had been interviewed, two managements of CEASAs, some agents who if had shown to potentials for the fresh vegetables distribution and non-small holders agriculture (patronal). To point out the reader to the studied sector, before the empirical analysis, a panorama of the marketing channels of fresh vegetables in São Paulo State was prepared. The sample included the main important involved in the distribution of fresh vegetables, except the final consumers, was possible to identify the currently channels used by the small holders agriculture, the main important agents in the marketing channel of these products and the requirements demanded for each agent. On the basis of such information, had been formulated some recommendations and suggestions about some alternatives channels for the distribution of fresh vegetables, as well as proposes for a better positioning of the small holder agriculture in the distribution of its products.
Keywords: Canais de distribuição; Agricultura familiar; Hortaliças; Marketing channel; Small holder agriculture; Fresh vegetable; ENGENHARIAS::ENGENHARIA DE PRODUCAO